Cost comparison of antihypertensive drugs available in India with Drugs Prices Control Order price list - Kumar, Rahul; Kumar, Narendra; Ahmad, Akhlaque; Kumar, Manoj; Nath, Rajendra; Dixit, Rakesh Kumar; Singh, Sarvesh (International Journal of Research in Medical Sciences, 2018)
Background: DPCO (Drugs Prices Control Order) price list is issued by NPPA (National Pharmaceutical Pricing Authority) each year to guide the pharmaceuticals companies for controlling the prices in India. Some drugs cost more than the DPCO list. As antihypertensive drugs are taken lifelong once diagnosis is made, price variation and costing above prescribed price cause a huge economic burden on such patients. This study was undertaken to know the number of antihypertensive drugs brands with price above the recommended DPCO price list 2017. Methods: Authors have collected the data from website medguideindia.com, CIMS (current index of medical specialties), Drug Today, and compared the listed antihypertensive drugs of various available brands in India with DPCO price list 2017. Data was entered in Microsoft excel 2010. Percentage of selling price above the DPCO price list was calculated for each drug. Results: The data of 30 formulations of 16 antihypertensive drugs was analysed. The total number of available brands of all formulations was 1365 out of which only 831 (60.88%) brands were found to have price <DPCO recommended list. 534 (39.12%) brands had price more than the recommended limit. The minimum violation of price limit was found in case of metoprolol 25mg (6.66%) and maximum price violation was observed with spironolactone 25mg and sodium nitroprusside inj 10mg/ml. Conclusions: Reassessment and monitoring for implementation of DPCO price list should be done as still large number of brands are not following the regulations and are violating the limit set by NPPA/DPCO.